Wilful murder in the outback - Burnett, Arch, 1895- (Adelaide : I.P.P.S., 1973)
Reminiscences of life in the outback during the early decades of the twentieth century; includes encounters with Aboriginal people.
Keywords: Central Australia. Personal observations; Settlement and contacts - Settlers; Mining industry - Opal; Race relations - Attitudes; Occupations - Pastoral industry workers - Drovers / Stockmen; Australia, Central; Strzelecki Creek (NE SA SH54-06); Umoona / Coober Pedy (West SA SH53-06); Innamincka (NE SA SG54-14); Cooper Creek (Qld Far West SG54, NE SA SH54)